Clinicopathological features and individualized treatment of kidney involvement in B-cell lymphoproliferative disorder - Nie, Guangyan; Sun, Lianqin; Zhang, Chengning; Yuan, Yanggang; Mao, Huijuan; Wang, Zhen; Li, Jianyong; Duan, Suyan; Xing, Changying; Zhang, Bo (Frontiers in Immunology, 2022)
Background Due to the various clinical and pathological manifestations of kidney involvement in lymphoproliferative disorder (LPD), the whole spectrum of kidney disease in LPD is still unclear, and data on kidney prognosis is scarce. Methods We retrospectively reviewed the renal pathology profiles from January 2010 to December 2021, and 28 patients with B-cell LPD combined with intact renal biopsy data were included. Results There were 20 men and 8 women aging 41 to 79 years at the time of renal biopsy (median age 62 years). According to hematological diagnosis, patients were classified into 4 groups: chronic lymphocytic leukemia (group1, n=7), Waldenström macroglobulinemia/lymphoplasmacytic lymphoma (group 2, n=8), other non-Hodgkin's lymphomas (group3, n=7; diffuse large B-cell lymphoma, n=2; MALT lymphoma, n=4; low grade B-cell lymphoma, n=1), and monoclonal gammopathy of undetermined significance (group 4, n=6). Median serum creatinine (Scr) level was 129 (range,59-956) umol/L. 8 patients (29%) were presented with acute kidney injury, and 5 patients (18%) required hemodialysis upon admission. Twenty-three patients (82%) presented with proteinuria (median protein excretion, 2.14 g/d), 11(39%) of whom had the nephrotic syndrome. Interstitial malignant infiltration was the most frequent renal lesion (n=6). Eight patients underwent immunohistochemistry of renal tissues, 3 of them with a light microscopic diagnosis of interstitial nephritis had immunohistochemical confirmation that the interstitial infiltrates were tumor cells. In addition, 2 patients with a light microscopic diagnosis of interstitial nephritis, immunohistochemistry was considered unrelated to lymphoma. The most common glomerular diseases were renal amyloidosis (n=4) and membranous nephropathy (n=4). The median follow-up time was 11 months. Of these, 6 had achieved hematological response, complete response in 5 cases. 8 had achieved renal response. At the end-of-study visit, 4 patients had died and 2 had progressed to end stage kidney disease (ESKD). Conclusion In conclusion, the clinicopathological spectrum of renal involvement in BLPD is diverse. Renal biopsy and immunohistochemistry are required for early diagnosis and prognostic assessment.